2021
DOI: 10.48550/arxiv.2107.13267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strong decays of the $P_{cs}(4459)$ as a $Ξ_c\bar{D}^{*}$ molecule

Feng Yang,
Yin Huang,
Hong Qiang Zhu

Abstract: In this work, we study the strong decay of the newly observed P cs (4459) assuming that it is a pure Ξ c D * molecular state. Considering two possible spin-parity assignments J P = 1/2 − and J P = 3/2 − the partial decay widths of the Ξ c D * molecular state into J/ψΛ, D − s Λ + c , and DΞ ( ′ ) c final states through hadronic loops are evaluated with the help of the effective Lagrangians. In comparison with the LHCb data, the spin-party J P = 1/2 − the assignment is preferred while this of J P = 3/2 − is disf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…[10] concluded that the P cs (4459) state was not a pure D * Ξ c molecular state. This is the same with our result [8] that the P cs (4459) can be explained as S -wave coupled molecular state with J P = 3/2 − . And we also proposed that a pure D * Ξ c molecular state with mass about 4459 and J P = 1/2 − could exist, and it mainly decays to Ξ ′ c D final state.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…[10] concluded that the P cs (4459) state was not a pure D * Ξ c molecular state. This is the same with our result [8] that the P cs (4459) can be explained as S -wave coupled molecular state with J P = 3/2 − . And we also proposed that a pure D * Ξ c molecular state with mass about 4459 and J P = 1/2 − could exist, and it mainly decays to Ξ ′ c D final state.…”
Section: Introductionsupporting
confidence: 93%
“…And the partial decay width of the molecular P cs (4459) into J/ψΛ is predicted to be larger for the J P = 3/2 − configuration than the J P = 1/2 − case, in agreement with the conclusions in Refs. [6,8]. With the quasipotential Bethe-Salpeter equation approach, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…With a value of the cutoff Λ = 0.9 − 1.1 GeV, the corresponding coupling constants shown in Fig 4. We note that they decrease slowly with the increase of the cut-off, and the coupling constant is almost independent of Λ, where the Y(4274) is P−wave D s D s0 (2317) molecular state. According to the studies in Refs [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] , a typical value of Λ = 1.0 GeV is often employed. Thus, in this work we take Λ = 1.0 GeV and the corresponding coupling constants are g YD s D s0 = 9.47 +0.79 −0.64 GeV 1/2 , which the error reflects variation in Λ from 0.9 to 1.1 GeV.…”
Section: Resultsmentioning
confidence: 99%
“…The introduced correlation function also makes the Feynman diagrams ultraviolet finite. Here we choose the Fourier transformation of the correlation to be a Gaussian form in the Euclidean space [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] ,…”
Section: Formalism and Ingredientsmentioning
confidence: 99%
See 1 more Smart Citation